Semiotika Tanda Verbal dan Tanda Visual Iklan Layanan Masyarakat - Tinarbuko, Sumbo (PANGGUNG, 2016)
ABSTRACTÃÂ This article uses qualitative ÃÂ research method by describing, interpretating, ÃÂ and explaining theÃÂ  connotation ÃÂ meaning ÃÂ of public ÃÂ service ÃÂ advertisingLaterÃÂ  ÃÂ on it is classified ÃÂ based on ÃÂ the sociolinguistics, ÃÂ pragmatics, visual communication ÃÂ design, and semiotics theory.The method of semiotics ÃÂ visual ÃÂ communication ÃÂ analysis ÃÂ is also used as an analysis method for verbal and visual ÃÂ data. It is used as one of public service advertising ÃÂ reading ÃÂ methods do to the tendency to see things, ÃÂ such as art, culture, social, visual communication design, and public service advertising ÃÂ as the phenomenon ÃÂ of language ÃÂ and sign.It is important to understand the semiotics of visual ÃÂ communication ÃÂ theory, because it can be used to enlarging ÃÂ the imagination,ÃÂ  ÃÂ insight, and ÃÂ knowledge about ÃÂ the importance ÃÂ of under- standing ÃÂ semiotics ÃÂ of visual communication, ÃÂ both on the creation ÃÂ and designing public service advertising ÃÂ process or process ÃÂ of reviewing ÃÂ the public service advertising object. Practically, ÃÂ it gives a positive adventage for the advertising ÃÂ practitioners ÃÂ or studentsÃÂ ÃÂ ÃÂ  at the Department ÃÂ of Advertising and Visual Communication Design.ÃÂ Keywords: sign, code and meaning ÃÂ of public service advertising, ÃÂ semiotics ÃÂ of visual ÃÂ communica- tion, verbal message and visual messageÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ ÃÂ Tulisan ini menggunakan metode penelitian kualitatif dengan cara mendeskripsikan, menginterpretasikan, dan menerangkan makna konotasi iklan layanan masyarakat yang kemudian diklasifikasikan berdasarkan pada bangunan teori sosiolinguistik, teori pragmatik, teori desain komunikasi visual, dan teori semiotika.Metode analisis semiotika komunikasi visual juga dimanfaatkan sebagai metode analisis data verbal dan data visual, sebagai salah satu metode pembacaan Iklan Layanan Masyarakat (ILM) akibat adanya kecenderungan untuk memandang berbagai hal, seperti seni, budaya, sosial, desain komunikasi visual, dan ILM sebagai fenomena bahasa dan tanda.Penguasaan teori semiotika komunikasi visual ini penting karena dapat digunakan sebagai bahan referensi verbal dan visual bagi khalayak untuk memperluas imajinasi, wawasan, dan pengetahuan mengenai pentingnya memahami semiotika komunikasi vi- sual baik dalam proses penciptaan dan perancangan iklan layanan masyarakat maupun proses mengkaji objek iklan layanan masyarakat. Secara praktikal memberikan manfaat yang positif baik bagi praktisi periklanan dan biro iklan pada umumnya maupun civitas akademika Jurusan Periklanan dan Desain Komunikasi Visual pada khususnya.ÃÂ Kata kunci: tanda, kode dan makna iklan layanan masyarakat, semiotika komunikasi visual, pesan verbal, dan pesan visual